OPTIMALISASI SUMBER DAYA TEKNOLOGI PT PINDAD MELALUI DIVERSIFIKASI KERJASAMA TERINTEGRASI DALAM UPAYA PEMENUHAN KEBUTUHAN ALUTSISTA TNI AL - Khaerul Bhakti (STMIK Mardira Indonesia, Bandung, 2022)
The TNI is a state instrument that has the duty and function to maintain the sovereignty and stability of security in the country, therefore it is necessary to have strong support for the TNI, especially in supporting the fulfillment of defense equipment needs. The perceived budget limitations in the defense sector make the TNI must be able to carry out its duties and functions by taking advantage of the existing Alutsista and its periodic additions. The Indonesian Navy is one of the three dimensions of the Indonesian National Armed Forces which can be said to have yet to fully possess an adequate Alutsista, so it can be said that the status of the Indonesian Navy's Alutsista is still lagging behind other countries in Asia in general. Therefore, it is important for the Navy to build strategic cooperation with the domestic defense industry such as PT Pindad, especially cooperation in an effort to improve the technological capabilities of state industrial companies so that they are able to produce defense products that are able to meet the needs of the TNI absolutely so that they no longer depend on imports of defense equipment from companies. - foreign defense industry companies. In this study, the method used is descriptive qualitative where data analysis is carried out using SWOT analysis by determining external and internal factors which are then formulated strategies for both short-term, medium-term and long-term strategies. The results of the study show that external factors are more dominant in determining the strategy that is set so that policy steps are needed that support existing opportunities so that they can be utilized properly and suppress threats that can occur by making existing threats as opportunities. Keywords: optimization, technology, cooperation, defense equipment